No evidence of association between mutant alleles of the CYP27B1 gene and multiple sclerosis. Issue 3 (26th February 2013) - Ban, Maria; Caillier, Stacy; Mero, Inger‐Lise; Myhr, Kjell‐Morten; Celius, Elisabeth G.; Aarseth, Jan; Torkildsen, Øivind; Harbo, Hanne F.; Oksenberg, Jorge; Hauser, Stephen L.; Sawcer, Stephen; Compston, Alastair
<x xml:space="preserve">Abstract</x> An association has previously been reported between susceptibility to multiple sclerosis and the rare mutant alleles of the CYP27B1 gene responsible for autosomal recessive vitamin D–dependent rickets type 1 (VDDR1). In an attempt to replicate this finding, we screened 495 multiplex families and 2, 092 single affected families, together with 4, 594 cases and 3, 583 controls (a total of 17, 073 individuals) but were unable to find any evidence supporting this putative association. Our data do not indicate that mutations responsible for VDDR1 influence the risk of developing multiple sclerosis. ANN NEUROL 2013;73:430–432